Manifestasi Qur’an Surat Al-Ahqaf (13-14) pada Upaya Membangun Perilaku Istiqomah pada Proses Menghafal Al-Qur’an di SD Takhassus Al-Qur’an Wonosobo - Khasib, Muhammad; Nasokah; Munawaroh, Hidayatu (Indonesian Journal of Islamic Elementary Education, 2023)
As a Quran memorizer, having the quality of steadfastness (istiqomah) is an imperative. During the process, there are several challenges encountered in manifesting steadfastness in memorization. The aim of this research is to understand the behavior of steadfastness in the Quran memorization process, along with the inhibiting and supporting faktors, as well as how the manifestation of QS: 46 (13-14) contributes to building steadfastness behavior in the Quran memorization process at SD Takhassus Al-Qur'an in Wonosobo. This study delves into the background situation extensively and the interactions of individuals, their social contexts, and groups. The research results show that the manifestation of the verses in QS: 46 (13-14) can boost the motivation of children to remain steadfast in Quran memorization, underpinned and supported by school rules, dormitory regulations, as well as the guidance of teachers and dormitory supervisors, who play a pivotal role in the successful implementation of Quranic verses for the benefit of the children during the memorization process.